136 Long term efficacy of catheter ablation for AF: impact of additional targeting of fractionated electrograms. (22nd September 2015) - Hunter, R J; Berriman, T J; Diab, I; Baker, V; Finlay, M; Richmond, L; Duncan, E; Kamdar, R; Thomas, G; Abrams, D; Dhinoja, M; Earley, M J; et al.
Abstract : Introduction: Published long term follow-up data for catheter ablation (CA) of AF is scarce. Although many centres perform ablation of complex fractionated electrograms (CFE) in addition to pulmonary vein isolation (PVI), evidence for this is conflicting. We sought to investigate long term efficacy of CA for AF and the impact of ablating CFE in addition to PVI and linear lesions in persistent AF (PeAF). Methods: Consecutive cases from 2002 to 2007 at St Bartholomew's Hospital were analysed. All patients underwent wide area circumferential ablation with confirmation of electrical isolation. For PeAF linear lesions were added at the roof and mitral isthmus, with additional targeting of CFE from 2005. Data were collected in a prospective database. Attempts were made to contact all patients for follow-up in September 2009. Failure was defined as documented recurrence of AF or other atrial tachyarrhythmia (AT) lasting ≥30 s. As repeated procedures for patients with recurrence of AF/AT can distort patterns of late recurrence, this was analysed following the first cluster of procedures defined as when the patient first emerged from their 3 month blanking period free of AF/AT (or failure accepted), that is, when AF was first successfully eliminated whether after one CA or several. Results: Two hundred eighty-five patients underwent 530 procedures. Mean age was 57±11 years, 75% male, 20% had structural heart disease and 53% paroxysmal AF. Left atrial diameter was 4.3±0.8 cm and 17% had left ventricular systolic dysfunction. Mean number of procedures was 1.9 per patient (1.7 for PAF and 2.0 for PeAF). Procedural complications included stroke or TIA in 0.6% (all of which resolved) and pericardial effusions which were drained without sequelae in 1.7%. There were no peri-procedural deaths. Of 285 patients, 270 were contacted for follow-up. During 3.3 (2.4 to 7.5) years from the first procedure, there were seven deaths (unrelated to their ablation or AF) and three strokes or TIA (0.3% per year). Freedom from AF/AT at 2.7 (0.2 to 7.4) years after the last procedure was 86% for PAF and 68% for PeAF. Most recurrence occurred in the first year, with late recurrence >3 years occurring in 3/100 years of follow-up. Kaplan–Meier analysis showed that CFE ablation improved outcome for PeAF after the first cluster of procedures (p=0.04), with a trend towards improved final outcome (p=0.13). Conclusion: Long term freedom from AF is achievable in the majority of patients with PAF and PeAF with low rates of late recurrence. Rates of periprocedural complications are low, and late adverse events including stroke are few. Targeting CFE in addition to PVI and linear lesions improves outcome for PeAF.